Charlie Wilson's war [videorecording (DVD)] - Hanks, Tom; Nichols, Mike; Adams, Amy; Roberts, Julia, 1967-; Hoffman, Philip Seymour, 1967-2014; Crile, George (Universal Studios Home Entertainment, 2007)
In the early 1980s, Charlie Wilson is best known as a womanizing US congressional representative from Texas. He seemed to be in the minor leagues, except for the fact that he is a member of two major foreign policy and covert-ops committees. However, once Charlie is prodded by his major conservative supporter, Joanne Herring, Wilson learns about the plight of the people who are suffering from the effects of the brutal Soviet occupation of Afghanistan. With the help of the maverick CIA agent, Gust Avrakotos, Wilson dedicates his canny political efforts to supply the Afghan mujahideen with the weapons and support needed to defeat the Soviet Union. Ultimately, Charlie learns that while military victory can be obtained, there are other consequences and prices to that fight that are ignored to everyone's sorrow. Based on a true story.